Reproduction Performances of Mud Crab (Scylla olivacea) Broodstocks with Different Feeds - Herlinah Herlinah; Early Septiningsih (Hasanuddin University, 2015)
Broodstock maturation diets is important research in order to increase the reproduction performance of spawning females. This research was conducted to determine the appropriate feed for mud crab broodstock spawned and as information in support of efforts to provide quality stem in a controlled manner. The study was conducted at the Installation Research Marana Institute For Coastal Aquaculture (RICA). The test animals that used were 15 ind. mud crab broodstock having of size 200±15 g, carapace length 6±0,5cm, carapace width 12±0,5 cm with gonadal maturity level (TKG I) obtained from crab fishing locations. Research using completely randomized design which consists of 3 treatments and 5 replications. The treatments tested were: A (trash fish), B (squid) and C (golden apple snail). Variable measured were the rate of gonadal maturity, egg diameter, the degree of spawning, embryo incubation period, the number of larvae, hatching rate, larval amino acid and proximate analyze content and water quality variables. The results of proximate analyze showed that trash fish have the highest fat content (7.85 %) while the squid had a high protein content (73.72 %). Amino acids contained in squid is alanine, cystine, and leucine are thought to have an important role in the maturation of the gonads crab. The feed squid gives the best performing for mud crab S.olivacea broodstockin the achievement of gonadal maturity stage, fecundity and hatching rate.